Bortezomib inhibits hepatocellular carcinoma via the Hippo‐Yes‐associated protein signalling pathway. Issue 4 (15th January 2023) - Liao, Yu; Hu, Kejun; Liu, Wangwang; Wang, Wei; Qiu, Huanhuan; Pan, Shumin; Lv, Qi; Xu, Guanglin
Abstract: Hepatocellular carcinoma (HCC) is one of the principle causes of cancer‐associated death throughout the world. However, the patients with HCC are insensitive to traditional drugs and lack effective therapeutic drugs. Dysregulation of Hippo‐Yes‐associated protein (YAP) signalling is closely associated with HCC. Bortezomib (BTZ) is mainly used in clinical multiple myeloma. It has recently been confirmed that BTZ could suppress cell proliferation in many different types of cancer. Nevertheless, the precise effects of BTZ on HCC and its possible interactions with the Hippo‐YAP signalling pathway in HCC cells remain largely unknown. In this study, HCC cell lines (HepG2 and Huh7) and nude mice with xenograft tumours were used to evaluate the influences of BTZ. Furthermore, we focused on exploring whether BTZ exerts its anti‐HCC effect through the Hippo‐YAP signalling pathway and aimed to lay a theoretical foundation for BTZ as a potential therapeutic drug for HCC. Herein, our results disclose a new mechanism of BTZ in controlling the cell growth of HCC. BTZ downregulates the level of YAP by promoting LATS1 expression to inhibit the growth of HCC cells, which leads to the phosphorylation of YAP and limits YAP nuclear translocation. In sum, our data confirmed that the Hippo‐YAP signalling pathway mediates the anti‐HCC effects of BTZ.